Leadership in Action : Issues and Observations - The Gap Between Personal and Organizational Values - Brightman, Jerry (Center for Creative Leadership, 1999)
The more proactive the leader in creating, sustaining, and communicating the vision, the more effectively he or she can close value gaps.